19 Challenges to recognising the dying patient in acute care – perceptions of senior and newly graduated scottish doctors. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Qureshi, SP; Jones, D; Skinner, J; Wood, M
Abstract : Background: Best practice guidelines emphasise timely recognition of dying patients. Continuing futile treatments may reduce the quality of the patient's remaining life. This qualitative study aimed to investigate perceived challenges for doctors in acute specialties when recognising dying. Methods: Semi-structured interviews were carried out with junior (UK Foundation trainees) and senior doctors (consultant in hospital specialties) across South East Scotland. Interviews were recorded, transcribed verbatim and data underwent thematic analysis. Participants have been anonymised through use of pseudonyms. Results: Fifteen junior doctors and thirteen senior doctors have been recruited. All participants described challenges in recognition of dying. Themes emerging from the junior interviews indicate challenges related to perceived dearth of undergraduate preparation; shift patterns leading to poor continuity of care and decision making often only at the point of patient deterioration; uncertainty over level of responsibility for re-evaluating aims of treatment. Senior participants described learning to recognise dying and futility of treatment as having occurred tacitly, and not being explicitly taught. Despite this, seniors described frequent uncertainty in practice, and perceived particular challenges with patients with whom they had long relationships. However, seniors believed that it is the consultant responsibility to diagnose dying and/or withdraw treatments. Both juniors and seniors described being less inclined to diagnose dying if the patient is young and/or has young children. Conclusions: This study has revealed challenges in recognition of dying perceived by Scottish doctors. The findings suggest this area of patient care is complex and uncertain, even for experienced practitioners. Comparing perceptions of senior and junior doctors gives insights for potential means of improved medical education. Recommendations include clearly defining the responsibilities of junior and senior team members, being explicit with learners about the often uncertain nature of recognising dying, and improved organisational factors to facilitate continuity of care.